Elevated Platelet‐to‐Lymphocyte Ratio as a Predictor of All‐Cause and Cardiovascular Mortality in Hypertensive Individuals - Rui Xu; Ling Chen; Changshun Yan; Hong Xu; Guiqiu Cao (The Journal of Clinical Hypertension)
ABSTRACT The platelet‐to‐lymphocyte ratio (PLR) has been proposed as a promising inflammatory biomarker, with potential implications for cardiovascular prognosis. However, its association with mortality outcomes in hypertensive individuals is not fully elucidated. This investigation sought to clarify the linkage between PLR and both overall and cardiovascular mortality in hypertensive individuals. Data from 15 483 hypertensive adults in the NHANES (2005–2018) were analyzed. Mortality data, including all‐cause and cardiovascular deaths, were sourced from the National Death Index (NDI) up to December 31, 2019. The linkage between PLR and mortality risk was depicted using restricted cubic spline (RCS) models. Cox proportional hazards regression models assessed the independent association of PLR with mortality risk, with adjustments incrementally applied: Model 1 without adjustments; Model 2 adjusted for age and sex; Model 3 adjusted further for age, gender, race, marital status, diabetes, alcohol intake, smoking status, body mass index (BMI), history of cardiovascular disease (CVD), high‐density lipoprotein cholesterol (HDL), low‐density lipoprotein cholesterol (LDL), total cholesterol (TC), triglyceride (TG), and creatinine (CR). Over a median follow‐up of 79 months, there were 2820 all‐cause deaths and 758 cardiovascular deaths. The multivariate Cox analysis showed that those in the highest PLR quartile had significantly elevated risks of all‐cause mortality (Model 1: HR = 1.28, 95% CI 1.16–1.42, p < 0.001; Model 2: HR = 1.14, 95% CI 1.03–1.26, p = 0.014; Model 3: HR = 1.16, 95% CI 1.05–1.29, p = 0.004)and cardiovascular mortality (Model 1: HR = 1.59, 95% CI 1.30–1.94, p < 0.001; Model 2: HR = 1.38, 95% CI 1.13–1.68, p = 0.001; Model 3: HR = 1.47, 95% CI 1.20–1.80, p < 0.001). The study reveals a U‐shaped relationship between PLR and all‐cause mortality, alongside a linear association with cardiovascular mortality. A PLR threshold of 118.83 has been identified as indicative of an adverse prognosis for all‐cause mortality. Elevated PLR independently predicts heightened risks of both all‐cause and cardiovascular mortality among hypertensive patients.